Quantitative label-free imaging of iron-bound transferrin in breast cancer cells and tumors - Ting Chean Khoo; Kate Tubbesing; Alena Rudkouskaya; Shilpi Rajoria; Anna Sharikova; Margarida Barroso; Alexander Khmaladze (Redox Biology, 2020)
Transferrin (Tf) is an essential serum protein which delivers iron throughout the body via transferrin-receptor (TfR)-mediated uptake and iron release in early endosomes. Currently, there is no robust method to assay the population of iron-bound Tf in intact cells and tissues. Raman hyperspectral imaging detected spectral peaks that correlated with iron-bound Tf in intact cells and tumor xenografts sections (~1270-1300 cm−1). Iron-bound (holo) and iron-free (apo) human Tf forms were endocytosed by MDAMB231 and T47D human breast cancer cells. The Raman iron-bound Tf peak was identified in cells treated with holo-Tf, but not in cells incubated with apo-Tf. A reduction in the Raman peak intensity between 5 and 30 min of Tf internalization was observed in T47D, but not in MDAMB231, suggesting that T47D can release iron from Tf more efficiently than MDAMB231. MDAMB231 may display a disrupted iron homeostasis due to iron release delays caused by alterations in the pH or ionic milieu of the early endosomes. In summary, we have demonstrated that Raman hyperspectral imaging can be used to identify iron-bound Tf in cell cultures and tumor xenografts and detect iron release behavior of Tf in breast cancer cells.